PENGARUH TINGKAT PENGANGGURAN TERDIDIK TERHADAP PERTUMBUHAN EKONOMI DIKOTA TANGERANG - Ropiah, Siti; Syamiya, Estu Niana (Journal of Business Education and Social, 2022)
The Influence of Educated Unemployment Rate on Economic Growth in Tangerang City. The purpose of this study is to determine the effect of the level of educated unemployment on economic growth.This research was conducted in the Tangerang and Cipondoh sub-districts in Tangerang City. The purpose of this study is to determine the level of educated unemployment that occurs in two sub-districts, whether the level of educated unemployment has an impact on growth in the two sub-districts in Tangerang City.The method in this study uses descriptive correlational analysis of the Quantitative type. Basically to explain the relationship between the factors or various variables that influence the variable level of educated unemployment on economic growth. The number of samples studied was 100 respondents who were from 50 Tangerang sub-districts and 50 Cipondoh sub-districts in Tangerang City.Based on this research, it can be concluded that the value carried out in the T test shows that the estimation results of the regression model produce a positive educated unemployment coefficient (0.706) with a sig probability value = 0.000 < Î± (0.05), then Ho is rejected and Ha is accepted. So, based on the test results, it can be concluded that partially educated unemployment has a positive and significant effect on economic growth in the two sub-districts in Tangerang City.